2015
DOI: 10.1088/2040-8978/18/2/024002
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of surface plasmon polariton modes with multiple nitrogen vacancy centers in single nanodiamonds

Abstract: Abstract:Nitrogen-vacancy (NV) centers in diamonds are interesting due to their remarkable characteristics that are well suited to applications in quantum-information processing and magnetic field sensing, as well as representing stable fluorescent sources. Multiple NV centers in nanodiamonds (NDs) are especially useful as biological fluorophores due to their chemical neutrality, brightness and room-temperature photostability. Furthermore, NDs containing multiple NV centers also have potential in high-precisio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In an attempt to overcome the limitations of Au and Ag, it has been suggested that aluminum (Al) may be used as the material of choice for plasmonic devices in the visible and UV regimes, in which photon energies are higher than the Al interband transition energy, leading to a reduced absorption as compare with Au or Ag. In this work we demonstrate experimentally the realization of aluminum plasmonic waveguides in a V-groove geometry, while our experiments are further supported by simulations. Previous studies have shown that V-groove plasmonic waveguides can be easily fabricated, allow efficient coupling even without the use of grating couplers, can support highly confined CPP modes in the near IR when coated with Au, and offer a wide range of possibilities for plasmonic circuitry and manipulation of light in the nanoscale. We show that V-groove plasmonic waveguides made of Al can support well-confined CPP modes at the short visible wavelength regime. The availability of such V groove based Al plasmonic waveguides enables interesting applications in areas such as quantum plasmonics, light harvesters, lab on chip components, as well as to the fundamental understanding of plasmon excitations and their interactions …”
Section: Fabrication and Characterizationmentioning
confidence: 74%
“…In an attempt to overcome the limitations of Au and Ag, it has been suggested that aluminum (Al) may be used as the material of choice for plasmonic devices in the visible and UV regimes, in which photon energies are higher than the Al interband transition energy, leading to a reduced absorption as compare with Au or Ag. In this work we demonstrate experimentally the realization of aluminum plasmonic waveguides in a V-groove geometry, while our experiments are further supported by simulations. Previous studies have shown that V-groove plasmonic waveguides can be easily fabricated, allow efficient coupling even without the use of grating couplers, can support highly confined CPP modes in the near IR when coated with Au, and offer a wide range of possibilities for plasmonic circuitry and manipulation of light in the nanoscale. We show that V-groove plasmonic waveguides made of Al can support well-confined CPP modes at the short visible wavelength regime. The availability of such V groove based Al plasmonic waveguides enables interesting applications in areas such as quantum plasmonics, light harvesters, lab on chip components, as well as to the fundamental understanding of plasmon excitations and their interactions …”
Section: Fabrication and Characterizationmentioning
confidence: 74%
“…This optical confinement is known as plasmonic nanofocusing [40][41][42][43][44][45][46][47][48][49]. Recently, the excitation of surface plasmon-polariton modes with multiple NV centers in single nanodiamonds on a silver-dielectric interface was demonstrated [50].…”
Section: Resultsmentioning
confidence: 99%
“…However, the decay curve measured in the front-side geometry becomes faster than the reference sample emission decay curve. The decay spectra are fitted with a biexponential decay function, which yields two lifetime components (Kumar et al, 2015). The faster component τ 1 arises due to the presence of graphitic impurities whereas the slower component τ 2 is the actual lifetime of NV centers.…”
Section: Emission Decay Rate Measurementsmentioning
confidence: 99%